Ramblings of a Chemical Engineer: A Book Review (Asean Journal of Engineering Education, 2021)
Ramblings of a Chemical Engineer is significantly influenced by the author's personal experiences as a chemical engineer who has worked in a variety of chemical companies. It encompasses his college years, time as a university researcher, and professional career; it is told in a fast-paced way via a succession of vignettes that capture the highlights of the events that formed him into the professional chemical engineer he is today. It was his intention to present information about a profession in chemical engineering to potential students seeking degrees in chemical engineering. It also acts as a guide for aspiring chemical engineers and future engineers, emphasizing what they should aim for and how much fun this profession can be.
Keywords: chemical engineering; engineering student; process engineer; professional engineer